PENGARUH E-WOM TERHADAP KEINGINAN UNTUK MEMBELI DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI PADA PENGGUNA APLIKASI STEAM DI BANDA ACEH - Zaniel Alfian, Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract : The purpose of this study was to determine the effect of Electronic Word of Mouth Steam applications on the desire to buy with brand trust as a mediating variable. While the object of this study is an Electronic Word Of Mouth Steam application as an independent variable. Brand trust as a mediating variable and a desire to buy as a dependent variable.E-Wom is a statement made by an actual, potential, or consumer customer before about a product or company where this information is available to people or institutions through internet media. Data collection method used is a questionnaire as a research instrument, in which the sample in this study is 100 people. Data that has been collected is analyzed using SmartPLS 3.0 software. The results of the research shows that E-Wom has a significant influence on buying interest, E-Wom has a significant influence on brand trust, brand trust affects buying interest, and brand trust mediates E-Wom's influence on buying interest. Keywords: E-Wom, Brand trust, Buying Interest.